Theoretical training in physical education of higher educational establishments’ girl students - Y.V. Gordienko (Physical Education of Students)
Purpose: testing and analysis of theoretical-methodic training of girl students at physical education classes. Material: in the research 45 2 nd year girl students of 18-19 age, participated. One group dealt with power-lifting and volleyball. Second group - practiced trainings by usual academic program. Results: it was found that girl students’ theoretical knowledge corresponds to middle level. It was also established that increase of motivation for acquiring and mastering knowledge facilitates effectiveness of physical education trainings’ construction. Conclusions: absence of physical education theoretical knowledge or its low level in girl students sharply reduces effectiveness of training and education, weakens interest to physical exercises’ and sports’ practicing.